Answer:
the answer is A) h=3V/(Pi*r^2)
Explanation:
This question is asking to solve for h, the equation is allready solved for V.
to solve for h means to get h by itself on one side of the equation.
1) V=(1/3)*pi*r^2*h. Divide 1/3*pi*r^2 to the other side of the equation
2) V/(1/3)*pi*r^2=h. 1/3 on the bottom denominator means we can multiply the reciprocal to the bottom and the top and get an equivalent answer. In short, move the 3 from the 1/3 onto the top.
3) (3*V)/(pi*r^2)=h. Simplify.
4) 3V/(Pi*r^2)=h.